Nabokov's American gut. Issue 11 (1st November 2020) - Carver, Beci
ABSTRACT: Edmund Wilson wrote to Nabokov on 14th January 1946: 'I hear from people who have seen you that you are becoming stout, optimistic and genial – in other words, Americanized'. The rumour was true: Nabokov's relocation to America in the 1940s seemed to act in conspiracy with the swelling of his gut, such that by the time he achieved international fame as an anglophone American writer, his body had transformed. I will propose in this article that Nabokov's discomfort at his expansion is linked to his ambivalence about becoming American. When Wilson accused him of becoming Americanly stout in 1946, he squirmed: 'Thanks for your remarks (though I did not understand the one about my "americanization")'. It is my argument here that, in the middle years of the twentieth century, Nabokov underwent what Lauren Berlant has described in an essay on American obesity as a 'crisis of choosing and antiwill', and that this crisis reverberates through his accounts of food and fatness.